Waqf Conflict Resolution Through Mediation (Islamic And Bugis Norm Perspective) - Muhammad Majdy Amiruddin (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
The purpose of this study is to identify the causes of disputes and to describe the dispute resolution process through non-litigation mediation in Islamic and Local Norm Perspective. The type of research that compilers use is field research, namely by obtaining data from interviews, observations, and related file searches. Furthermore, this research is supported by library research as a complement. The approach in this study is a juridical-empirical approach. The results of the study concluded that  The dispute that occurred was related to the status of the land that was built on top of the Madrasah DDI Labukkang. The cause of the dispute is based on two theories, the theory of Principle negotiation and the Theory of basih human needs. The mediation process is carried out through 3 stages. First is pre-mediation. Mediation conducts the plans related to the preparation of mediation. Second is the execution of mediation. The mediator presents the disputing parties, gives an opportunity to all parties to provide information. The last is the emplementation of mediation. From the syariah perspective, the mediation complies with the 12 basic principles in Islamic Mediation. From the Bugis Norms, it complies with the five norms called pangngadareng.